A QM:MM model for the interaction of DNA nucleotides with carbon nanotubes1. Issue 11 (21st March 2015) - Chehel Amirani, Morteza; Tang, Tian
<x xml:space="preserve">Abstract</x> Hybrid materials formed by DNA and carbon nanotubes (CNTs) have shown very interesting properties, but their simulation in solution using quantum mechanical approaches is still a challenge in the computational chemistry community.